2015
DOI: 10.5433/1679-0359.2015v36n5p3481
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and energetic values of wheat and its sub-products for broiler chicken

Abstract: The objective of this study was to determine the chemical composition, apparent metabolizable energy (AME), AME corrected by nitrogen retention (AME n ) and metabolization coefficients (MC and MC n ) of different feeds for broilers from the western region of Paraná State. The experiment was conducted at the Physiology of Birds Laboratory at UNIOESTE. Two hundred and sixty male chicks of the Cobb 500 strain, at 21 days old, were distributed in a randomized design with 12 treatments and four replicates of five b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Nunes et al (2001), in turn, observed 4339 kcal.kg -1 AMEn and 97.90% CAMEn in biscuit waste used in broiler diets. Broch et al (2015) investigated the metabolizability of energy from wheat and its derivatives and found variations of 42 to 73% for CAMEn, due to differences in the composition and utilization of the feedstuffs. Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nunes et al (2001), in turn, observed 4339 kcal.kg -1 AMEn and 97.90% CAMEn in biscuit waste used in broiler diets. Broch et al (2015) investigated the metabolizability of energy from wheat and its derivatives and found variations of 42 to 73% for CAMEn, due to differences in the composition and utilization of the feedstuffs. Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…According to Rostagno et al (2017) bread waste meal (BWM) has an average standardized ileal digestibility coefficient of amino acids of 90.0% and 12.10% CP. However, bakery wastes such as breads and biscuits vary widely in their composition due to variations in the ingredients and additives used in their manufacture and variations in wheat (NUNES et al, 2001;BROCH et al, 2015). Because of this variability, the energy values and digestible amino acid contents of wheat by-products should be constantly updated.…”
Section: Introductionmentioning
confidence: 99%
“…This result can be justified because soluble fiber (NSPs) has a strong capacity for ionic bonds with mineral elements that negatively interfere with its absorption by poultry (Broch et al, 2015). In turn, xylanase enzymes are capable of catalyzing and releasing monosaccharide NSPs (Alagawany et al, 2018), preventing the deleterious effects on the absorption of minerals; the results observed in this study indicate that the overall improvement in metabolizability coefficients may have been influenced by the degradation of NSPs because the MCDM values show the metabolizability coefficients observed for PC, EE, NDF, and ADF.…”
Section: Test1mentioning
confidence: 99%
“…Ao determinar a energia metabolizável das aves, melhora-se a capacidade destes animais em aproveitar os nutrientes e energia fornecidos pelos alimentos, pois a digestibilidade de energia tende a aumentar com o desenvolvimento do seu trato digestivo ao avançar da idade (Broch et al, 2015).…”
Section: Sistema De Energia Para Avesunclassified